O Estado e o impacto social das cooperativas habitacionais - Silva, Ademir Alves da (1998)
The objective of this study was to research the social impact of housing cooperatives in Brazil through the historical factors and context in which they first appeared. The general analysis was followed by study and evaluation of a particular case, the "OSWALDO CRUZ COOPERATIVE" of São Paulo. The research on the micro-1evel ( the inhabitants concept about the cooperative itself and its consequent social impacts ) demanded a larger study about state and public policies which are viewed as fighting arenas among the different social classes. An analysis was a1so made of the beginning and evolution of the cooperativism thought in its various trends from brief historical references to the utopian socialism ideas, which have in the cooperativist movement one of its best expressions. This study was presented to examining board of the Pos-Graduate Studies Program in Social Work of PUC-SP as a requirement for a master's degree